Central African Republic : Request for a Three-Year Arrangement Under the Extended Credit Facility: Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Central African Republic. (IMF Staff Country Reports; Country Report ;, 2012)
Political and economic uncertainties in the Central African Republic (C.A.R.) have abated, but the sociopolitical environment remains fragile. Institutional weaknesses, limited and volatile aid flows, and persistently low domestic resource mobilization have slowed the efforts and considerable transition out of fragility. The resumption of donor budget support will close the financing gap and increase poverty and infrastructure spending. Implementation of structural reforms needs to be accelerated to support the government's medium-term objectives. Strengthening debt management capacity to effectively monitor debt development is essential.